Tiếng Việt và tin học, quan niệm, giải pháp và cài đặt - Thai, Tran Ba; Viet, Ngo Trung (Journal of Computer Science and Cybernetics, 2018)
Some research results about the introducing of Vietnamese characters into informatics, realized at the institute of informatics and cybernetics, are presented in this paper. Three levels of  research are  distingued and given in cetail.